Identification of validated questionnaires to measure adherence to pharmacological antihypertensive treatments - Pérez-Escamilla, B.; Franco-Trigo, L.; Moullin, Joanna; Martínez-Martínez, F.; García-Corpas, J. (Dove Medical Press, 2015)
© 2015 Pérez-Escamilla et al. Background: Low adherence to pharmacological treatments is one of the factors associated with poor blood pressure control. Questionnaires are an indirect measurement method that is both economic and easy to use. However, questionnaires should meet specific criteria, to minimize error and ensure reproducibility of results. Numerous studies have been conducted to design questionnaires that quantify adherence to pharmacological antihypertensive treatments. Nevertheless, it is unknown whether questionnaires fulfil the minimum requirements of validity and reliability. The aim of this study was to compile validated questionnaires measuring adherence to pharmacological antihypertensive treatments that had at least one measure of validity and one measure of reliability. Methods: A literature search was undertaken in PubMed, the Excerpta Medica Database (EMBASE), and the Latin American and Caribbean Health Sciences Literature database (Literatura Latino-Americana e do Caribe em Ciências da Saúde [LILACS]). References from included articles were hand-searched. The included papers were all that were published in English, French, Portuguese, and Spanish from the beginning of the database’s indexing until July 8, 2013, where a validation of a questionnaire (at least one demonstration of the validity and at least one of reliability) was performed to measure adherence to antihypertensive pharmacological treatments. Results: A total of 234 potential papers were identified in the electronic database search; of these, 12 met the eligibility criteria. Within these 12 papers, six questionnaires were validated: the Morisky–Green–Levine; Brief Medication Questionnaire; Hill-Bone Compliance to High Blood Pressure Therapy Scale; Morisky Medication Adherence Scale; Treatment Adherence Questionnaire for Patients with Hypertension (TAQPH); and Martín–Bayarre–Grau. Questionnaire length ranged from four to 28 items. Internal consistency, assessed by Cronbach’s a, varied from 0.43 to 0.889. Additional statistical techniques utilized to assess the psychometric properties of the questionnaires varied greatly across studies. Conclusion: At this stage, none of the six questionnaires included could be considered a gold standard. However, this revision will assist health professionals in the selection of the most appropriate tool for their individual circumstances.